Parental satisfaction with pediatric emergency care: a nationwide, cross-sectional survey in Korea - Hye Young Jang; Young Ho Kwak; Ju Ok Park; Do Kyun Kim; Jin Hee Lee (Korean Pediatric Society, 2015)
PurposeThis study attempted to examine parental satisfaction with pediatric emergency care (PEC) in Korea and investigate the features influencing overall satisfaction.MethodsA nationwide, cross-sectional survey was conducted among parents who had taken their children to an Emergency Department (ED) in the three years prior to the study. A 21-item, structured questionnaire was administered to the parents through a web-based system. Participants' satisfaction levels and the strength of the association between PEC components and overall satisfaction were rated using a 7-point Likert scale.ResultsIn total, 1,000 parents participated in the survey, of which 402 (40.2%) stated that they were generally satisfied with the delivered PEC. Female participants, mothers, and parents with low-acuity patients were more likely to be dissatisfied with the delivered PEC. Although the ED environment was the lowest level of satisfaction, it did not significantly influence the respondents' overall levels of satisfaction. The most influential factors in terms of overall satisfaction were "nurses' professionalism" and "doctors' attitude and proper explanation".ConclusionParents' overall level of satisfaction with PEC is relatively low and is closely related to factors associated with ED personnel.